Impostor Phenomenon Measurement Scales: A Systematic Review - Mak, Karina K. L.; Kleitman, Sabina; Abbott, Maree J. (Frontiers in Psychology, 2019)
The impostor phenomenon is a pervasive psychological experience of perceived intellectual and professional fraudulence. It is not a diagnosable condition yet observed in clinical and normal populations. Increasingly, impostorism research has expanded beyond clinical and into applied settings. However, to date, a systematic review examining the methodological quality of impostorism measures used to conduct such research has yet to be carried out. This systematic review examines trait impostor phenomenon measures and evaluates their psychometric properties against a quality assessment framework. Systematic searches were carried out on six electronic databases, seeking original empirical studies examining the conceptualization, development, or validation of self-report impostor phenomenon scales. A subsequent review of reference lists also included two full-text dissertations. Predetermined inclusion and exclusion criteria were specified to select the final 18 studies in the review sample. Of the studies included, four measures of the impostor phenomenon were identified and their psychometric properties assessed against the quality appraisal tool—Clance Impostor Phenomenon Scale, Harvey Impostor Scale, Perceived Fraudulence Scale, and Leary Impostor Scale. The findings often highlighted that studies did not necessarily report poor psychometric properties; rather an absence of data and stringent assessment criteria resulted in lower methodological ratings. Recommendations for future research are made to address the conceptual clarification of the construct's dimensionality, to improve future study quality and to enable better discrimination between measures.